2006
DOI: 10.3892/or.15.5.1265
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles with cDNA microarray reveal RhoGDI as a predictive marker for paclitaxel resistance in ovarian cancers

Abstract: Abstract. In the current study, we identified paclitaxelresistant related genes by comparing gene expression profiles of paclitaxel-resistant and parent ovarian cancer cell lines. Gene expression profiles of the human ovarian cancer cell line (KF28), cisplatin-resistant cell line (KFr13) induced from KF28, and paclitaxel-resistant cell lines (KF28TX and KFr13TX) induced by exposing KF28 and KFr13 to doseescalating paclitaxel were compared and analyzed using cDNA microarray. Of 557 human cancer-related cDNA tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 24 publications
0
30
0
1
Order By: Relevance
“…MDR-1 overexpression in ovarian cancer cell lines with paclitaxel resistance had been reported (Masanek et al, 1997;Duan et al, 1999). Similarly, we had also confirmed MDR-1 overexpression in paclitaxel-resistant derivative ovarian cancer cell line, KFr13 TX cells (Yamamoto et al, 2000b;Goto et al, 2006). The molecular mechanism of MDR-1 is still uncertain.…”
Section: Discussionmentioning
confidence: 58%
“…MDR-1 overexpression in ovarian cancer cell lines with paclitaxel resistance had been reported (Masanek et al, 1997;Duan et al, 1999). Similarly, we had also confirmed MDR-1 overexpression in paclitaxel-resistant derivative ovarian cancer cell line, KFr13 TX cells (Yamamoto et al, 2000b;Goto et al, 2006). The molecular mechanism of MDR-1 is still uncertain.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, gastric cancer cells isolated from patients with higher levels of RhoGDI2 were more resistant to 5-FU. Other groups have shown that RhoGDI2 was overexpressed in chemotherapy-resistant fibrosarcoma cells and paclitaxel-resistant ovarian cancers, respectively (16,17). However, Lee et al (18) recently revealed contradictory results suggesting that the chemo-resistance in ovarian serous carcinomas is associated with the downregulation of RhoGDI2 expression.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, the expression of ABCC3 and ABCC4 was decreased in the drug resistant cell lines. In a similar study of ovarian cancer cell line KF28 TX resistant to paclitaxel using an IntelliGene microarray (Table 2) containing 557 human cancer-related cDNAs including ABCB1 and ABCC3, ABCB1 was also found to be overexpressed and likely contribute to paclitaxel resistance [20]. Similar to the Clontech Rat cDNA array (see above), the usefulness of these arrays in ABC transporter profiling, however, is also limited.…”
Section: Identification Of Abc Transporter Genes In Drug-selected Celmentioning
confidence: 97%